Taylor Glacier Noble Gases - Younger Dryas - Shackleton, Sarah (IEDA: US Antarctic Program Data Center, 2019)
Abstract: Noble gas data from Taylor Glacier for mean ocean temperature reconstruction during the Younger Dryas. Also includes field measurements of methane and standard deviations of replicate CO2 measurements from WAIS Divide.